A Systematic Literature Review on The Relationship Between Sharia Financial Literacy and Students’ Personal Financial Management Behavior - Wiliana, Rahayu; Rachmadani, Febby (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2025)
This study aims to synthesize the theoretical evolution, assess the consistency of empirical findings, and identify moderating factors influencing university students’ personal financial management behavior. Employing a Systematic Literature Review (SLR) approach following the Kitchenham protocol and PRISMA framework, 13 selected articles from SINTA-indexed and related academic databases were critically examined. The findings indicate that the literature has evolved from predominantly normative–ideological perspectives toward more complex behavioral psychology models, although methodological approaches remain largely dominated by quantitative, verification-oriented designs. The influence of Islamic financial literacy on financial behavior demonstrates a moderate level of consistency, with its effectiveness largely contingent upon the transformation of knowledge into functional financial self-efficacy. Notably, significant divergence is observed in external moderating factors, where the social environment frequently exhibits insignificant effects, in contrast to locus of control, which consistently strengthens behavioral outcomes. Overall, the study concludes that Islamic financial literacy does not function as a deterministic panacea; rather, its effectiveness depends on the internalization of values that support self-regulation in mitigating consumptive risks in the fintech-driven financial landscape. The findings underscore the need for greater methodological diversification and the development of financial education strategies that emphasize psychological and behavioral dimensions beyond cognitive knowledge alone.